The politics of happiness : what government can learn from the new research on well-being - Bok, Derek Curtis (Princeton University Press, 2010)
During the past forty years, thousands of studies have been carried out on the subject of happiness. Some have explored the levels of happiness or dissatisfaction associated with typical daily activities, such as working, seeing friends, or doing household chores. Others have tried to determine the extent to which income, family, religion, and other factors are associated with the satisfaction people feel about their lives. The Gallup organization has begun conducting global surveys of happiness, and several countries are considering publishing periodic reports on the growth or decline of happ.